Sulfonated poly (ether sulfone)/poly (vinyl alcohol) blend membranes customized with tungsten disulfide nanosheets for DMFC applications. (24th October 2018) - Divya, Kumar; Sri Abirami Saraswathi, Meenakshi Sundaram; Alwarappan, Subbiah; Nagendran, Alagumalai; Rana, Dipak
Abstract: Sulfonated poly (ether sulfone) (SPES) and poly (vinyl alcohol) (PVA) blend nanocomposite proton exchange membranes were fabricated and tailored with exfoliated tungsten disulfide (E-WS2 ) nanosheets with the aim of achieving better methanol resistant properties for direct methanol fuel cell (DMFC) applications. Reinforcement due to the existence of E-WS2 nanosheets on composite membrane imparted superior mechanical and thermal stability. Surface morphology of the composite membranes in terms of roughness is examined by AFM. Further, the results confirmed the intercalation of E-WS2 nanosheets onto the polymer matrix. The incorporation of E-WS2 nanosheets onto SPES/PVA system shows highest proton conductivity of 1.18 × 10 −2 Scm −1 (at 25 °C) and mechanical stability of 143 MPa upon comparison with pristine SPES membrane. Furthermore, the methanol absorption by membrane matrix is found to be 3.42 × 10 −8 cm 2 s −1 . Overall results confirmed that SPES/PVA/E-WS2 nanocomposite proton exchange membranes are promising for applications in DMFCs. Graphical abstract: Highlights: High methanol resistant SPES/PVA/E-WS2 nanocomposite PEMs was effectively fabricated. SPW-3 PEM exhibited higher proton conductivity and selectivity whereas lower methanol permeability. SPES/PVA/E-WS2 nanocomposite PEMs were found suitable for use in DMFCs.